2008
DOI: 10.1152/ajplung.00062.2007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dynamic compression on lentiviral transduction in an in vitro airway wall model

Abstract: Tomei AA, Choe MM, Swartz MA. Effects of dynamic compression on lentiviral transduction in an in vitro airway wall model. Am J Physiol Lung Cell Mol Physiol 294: L79-L86, 2008. First published November 16, 2007 doi:10.1152/ajplung.00062.2007.-Asthmatic patients are more susceptible to viral infection, and we asked whether dynamic strain on the airway wall (such as that associated with bronchoconstriction) would influence the rate of viral infection of the epithelial and subepithelial cells. To address this, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…To date, relatively little attention has been paid to modeling at the cellular or subcellular level in the lung, or to in response to epithelial challenges including physical damage (Malavia et al, 2009;Thompson et al, 2006), viral infection (Tomei et al, 2008) or mechanical strain to simulate the effect of bronchoconstriction on the epithelium (Choe et al, 2003). Similarly, by co-culturing airway epithelial and endothelial cells, it has been shown that cell-cell communication involving soluble endothelial-derived factor(s) causes a significant reduction in paracellular permeability compared to that seen when epithelial or endothelial monolayers are studied in monoculture (Chowdhury et al, 2010).…”
Section: In Silico Modelingmentioning
confidence: 99%
“…To date, relatively little attention has been paid to modeling at the cellular or subcellular level in the lung, or to in response to epithelial challenges including physical damage (Malavia et al, 2009;Thompson et al, 2006), viral infection (Tomei et al, 2008) or mechanical strain to simulate the effect of bronchoconstriction on the epithelium (Choe et al, 2003). Similarly, by co-culturing airway epithelial and endothelial cells, it has been shown that cell-cell communication involving soluble endothelial-derived factor(s) causes a significant reduction in paracellular permeability compared to that seen when epithelial or endothelial monolayers are studied in monoculture (Chowdhury et al, 2010).…”
Section: In Silico Modelingmentioning
confidence: 99%
“…Bronchioconstriction can be mimicked by a co-culture in ALI of IMR-90 fibroblasts in collagen gel covered by normal bronchial epithelial cells in a strain device. In this device, cells are subjected to cyclic compression for 72 h [44]. …”
Section: In Vitro Systemsmentioning
confidence: 99%
“…Conversely, cyclical stretching of the epithelium can modulate prostanoid synthesis (169). Furthermore, dynamic compressive strain of the epithelial layer that is associated with bronchoconstriction of a circular airway can promote epithelial properties such as solute transport, viral gene delivery (199), and secretion of ECM-modifying proteins such as tissue factor (147). The mechanisms involved in mechanotransduction are still under investigation, but they could include Rho kinase (197), among other factors, which is in turn influenced by the ECM (154).…”
Section: Materials Matrix and Mechanobiologymentioning
confidence: 99%